ANALYSIS OF BUSINESS DEVELOPMENT AND INNOVATION: STRATEGIES FOR BUSINESS GROWTH, ENTREPRENEURSHIP, AND INNOVATION IN LOCAL AND INTERNATIONAL MARKETS - Robert Wu (Ecomind Press, 2025)
This paper investigates the strategic role of business development and innovation in fostering business growth, with a focus on entrepreneurship and market expansion in both local and international contexts. As companies navigate an increasingly globalized and competitive landscape, adopting innovative strategies becomes essential for sustaining growth and achieving market leadership. The research highlights how business development, entrepreneurship, and innovation intersect to drive success. Through an extensive literature review, survey analysis, and data analysis, the paper explores the best practices and strategies that businesses can implement to harness innovation and entrepreneurship effectively. This study also addresses the impact of technological advancements and regulatory factors on innovation in diverse market environments.